Enabling positive change: Progress and setbacks in HIV and sexual and reproductive health and rights. Issue 10 (3rd October 2018) - Mane, Purnima; Aggleton, Peter
ABSTRACT: At a point in history when the future of sexual and reproductive health including HIV looks particularly uncertain, it is helpful to recognise that many of the challenges currently faced are neither new nor insurmountable. Reflecting on past achievements and lessons learned helps us to have confidence that positive change is feasible. This paper reflects on some of the changes observed in countries like India and Mozambique and identifies a range of factors which need to coalesce to enable these developments, along with specific contextual factors. It is the combination of these influences rather than any one of them alone that brought about the change in the three instances described – fostering a positive political response to HIV in its early years in India; bringing about policy reform on abortion in Mozambique; and increasing contraceptive prevalence and age at marriage in some districts in Bihar, India. Change is always fragile and susceptible to setbacks, but change-seekers can learn in the process and gain renewed hope that progress can and often does take place if they persevere.